Modeling of proton-conducting solid oxide fuel cells fueled with syngas - Ni, M.; Shao, Zongping; Chan, K. (2014)
Solid oxide fuel cells (SOFCs) with proton conducting electrolyte (H-SOFCs) are promising power sources for stationary applications. Compared with other types of fuel cells, one distinct feature of SOFC is their fuel flexibility. In this study, a 2D model is developed to investigate the transport and reaction in an H-SOFC fueled with syngas, which can be produced from conventional natural gas or renewable biomass. The model fully considers the fluid flow, mass transfer, heat transfer and reactions in the H-SOFC. Parametric studies are conducted to examine the physical and chemical processes in H-SOFC with a focus on how the operating parameters affect the H-SOFC performance. It is found that the presence of CO dilutes the concentration of H2, thus decreasing the H-SOFC performance. With typical syngas fuel, adding H2O cannot enhance the performance of the H-SOFC, although water gas shift reaction can facilitate H2 production.